President Unveils Projects to Boost Teaching of STEM Subjects - Robelen, Erik W (Education Week, 2010)
President Barack Ohama has once again sought to promote greater attention to education in science, technology, engineering and mathematics, collectively known as the STKM fields, as he announced more than $250 million in private investments to help attract and prepare new teachers in those subjects and improve instruction by practicing teachers.